Development of underwater vehicle's application in offshore oil and study on the key problems of anti-disturbance control. Issue 1 (July 2021) - Geng, Wenbao; Lv, Xinze; Wang, Lin; Wang, Kejia; Xiao, Xinjie
Abstract: Underwater Vehicles are promising in offshore oil and gas development, but there are some problems. The beginning of the essay introduces the concept and classification of underwater vehicles. Then the application of underwater vehicle in offshore oil and gas is recommended. This paper briefly introduces the development status of underwater vehicle and the disadvantages of its application in offshore oil and gas engineering. The underwater vehicle needs to carry out fine detection and operation in oil and gas operation. In view of this requirement, the advantages and feasibility of anti-disturbance control in realizing high-precision control of underwater vehicle are analyzed in detail from the angle of motion control.